Confucian’s Revival and a Newly Established Confucian Institution in Purwokerto - Moh Zaenal Abidin Eko Putro (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
Two decades after the abolishment of the banning of Chinese cultural expression publicly in Indonesia’ Post-Reformasi, studies on the institutionalization of Indonesian Chinese including Confucians in Indonesia seem to have been very few if it compared with that of Indonesian Chinese’ freedom expression and state perceived Confucians in general. This paper portrays the revival of Confucians in Indonesia happened in Purwokerto City (Banyumas), Central Java of Indonesia, by looking at the establishment of a new Confucian organization, namely Perkumpulan Rohaniwan Agama Khonghucu Indonesia (Parakhin, or Association for Confucianism clerics in Indonesia). Based on a qualitative research, this paper explores the narration behind the establishment of Parakhin. The paper shows that the democratic society and democratic climate of Indonesia enable any society including Confucian to align with the freedom of expression albeit potentially violating the essential concept, that is loyalty and filial piety that are very salient in Confucianism.